Galia Muskmelons: Evaluation for Florida Greenhouse Production - Elizabeth M. Lamb; Nicole L. Shaw; Daniel J. Cantliffe; Jeanmarie M. Harty (EDIS)
Revised! HS-919, a 5-page illustrated fact sheet by Nicole L. Shaw, Daniel J. Cantliffe, and Jeanmarie M. Harty, evaluates the potential of this specialty melon prized for its bold aroma and high sugar content for greenhouse production in Florida, discussing production methods and cultivar evaluation. Published by the UF Department of Horticultural Sciences, June 2009.